1984
DOI: 10.1002/j.1460-2075.1984.tb01875.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological detection of left-handed Z DNA in isolated polytene chromosomes. Effects of ionic strength, pH, temperature and topological stress.

Abstract: We have searched for the presence of left‐handed Z DNA in unfixed polytene chromosomes isolated from the salivary glands of Chironomus thummi larvae. Physiological as well as fixation conditions were explored to assess the effects of a variety of factors known to influence the B‐Z equilibrium. At neutral pH and physiological ionic strength, a weak immunofluorescence staining confined to the periphery of chromosomal bands is elicited but only by using high concentrations of anti‐Z DNA immunoglobulin (IgG). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 71 publications
4
35
0
Order By: Relevance
“…It has been reported that brief preincubation of cells at low pH enhances the binding of anti-Z-DNA antibodies (17). We performed a series of experiments in which lymphocytes were pretreated with low-pH buffers, neutralized, and then exposed to the primary anti-Z-DNA antibodies (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that brief preincubation of cells at low pH enhances the binding of anti-Z-DNA antibodies (17). We performed a series of experiments in which lymphocytes were pretreated with low-pH buffers, neutralized, and then exposed to the primary anti-Z-DNA antibodies (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of nuclear Z-DNA, histone removal apparently induces negative supercoiling and stabilizes alternating purine-pyrimidine sequences in Z-conformations such that they are specifically recognized by anti-Z-DNA immunoglobulins in deproteinized cells (16). The existence of Z-DNA or Z-RNA in vivo has not been shown.…”
Section: Methodsmentioning
confidence: 99%
“…DNA sequences that are in the Z conformation (or that may be induced to adopt the Z conformation) have been identified in vivo (3)(4)(5)(6), and a role for Z DNA in the regulation of gene expression has been proposed (1).…”
mentioning
confidence: 99%